Аналіз впливу різних типів компоновки кузовів автобусів на особливості формування потоків повітря в умовах вимушеної конвекції салону - Голенко, Костянтин Едуардович; Войчишин, Юрій Іванович; Яковенко, Євгенія Ігорівна; Горбай, Орест Зенонович; Рудик, Олександр Юхимович (Національний технічний університет "Харківський політехнічний інститут", 2022)
В роботі запропонований аналіз впливу п'яти видів компоновки кузовів міських автобусів на формування потоків повітря в салоні, згенерованих вентилятором мотовідсіку в умовах вимушеної конвекції. Авторами проведено три типи випробувань з різними крайовими умовами у розрахунковому модулі ANSYS Fluent: вхідною швидкість потоків від вентилятора мотовідсіку, температурою потоків та середовища, внутрішньою та зовнішньою конвекцією. За результатами імітації натурних випробувань встановлено, що найбільш ефективним є варіант компоновки автобуса з розташуванням двигуна горизонтально у задньому звисі.

The paper proposes the influence analysis of five types of city bus body layouts on the air flows formation in the cabin, generated by the motor compartment fan under conditions of forced convection. The authors conducted three types of tests with different boundary conditions in the finite element calculation module of ANSYS Fluent: the input velocity of the flows from the motor compartment fan, the temperature of the flows and the environment, internal and external convection. According to the results of simulated field tests, it was established that the most effective is the layout of the bus with the engine located horizontally in the rear overhang. Such a layout is relatively expensive from the point of view of production, because it requires the installation of the opposite type of "boxer" engine in most cases, which is characterized by a higher cost, complexity of maintenance and is less common in contrast to V-type internal combustion engine schemes. However, air circulation occurs throughout the cabin the most effectively in this layout scheme, taking into account the driver's cabin and other locations. Layouts with central positioning of the engine (vertical and horizontal) also deserve attention – they ensure a symmetrical distribution of air in the front and rear of the bus body, which can be especially relevant in the cold period of the year.
Influence analysis of the different types bus body composition on the characteristics of the air flows formation in conditions of forced cabin convection
Keywords: салон; компонування; температура; швидкість повітря; температурна карта; конвекція; компоновка; міський автобус; салон автобусу; вентиляція; мікроклімат; interior; layout; temperature; air speed; temperature map; convection; layout; city bus; bus interior; ventilation; microclimate